Towards Capital Account Convertibility - Fischer, Bernhard (OECD Publishing, 1992)
• Advanced developing countries are increasingly encouraged to remove existing capital controls, but mixed experiences with capital account opening caution that reform must be carefully designed to increase efficiency and growth without compromising stability • A gradual dismantling of capital controls is recommended, based on progress made in tax reform, exchange rate management, enforcement of bank competition and supervision, and solving domestic banks' bad-loan problems
Keywords: Development